Detection of Circulating Tumor Cells and Its Application in Prostate Cancer - Song, Jin-Qi; Zhou, Ya-Nan; Tu, Gang-Liang; Xu, Chang-Li; Xu, Hui (Nepalese Journal of Cancer, 2020)
In recent years, circulating tumor cells have become the focus of tumor research. In-depth study of the role of circulating tumor cells in the genesis, development, and evolution of tumors will be of great significance for the early detection, early diagnosis, early treatment, and prognosis of tumors. Prostate cancer is one of the common male malignant tumors, and the role of circulating tumor cells in prostate cancer has been increasing year by year. This article will focus on the progress of circulating tumor cells detection and its application in prostate cancer.